Homoclinic Bifurcation and Endogenous Cycles in the Dynamic IS-LM Model - Bella, Giovanni (Journal of Reviews on Global Economics, 2015)
This paper contributes to the new keynesian literature by showing that stable endogenous cycles can emerge as equilibrium solutions of the traditional IS-LM model. The application of the original Bogdanov-Takens theorem allows us to determine the regions of the parametric space where the model exhibits a global indeterminate solution, and a low-growth trapping region, characterized by a continuum of equilibrium trajectories in the proximity of a homoclinic bifurcation.